2020
DOI: 10.1002/msc.1519
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of UK student physiotherapists' goal setting practices within anterior cruciate ligament rehabilitation

Abstract: Background Anterior cruciate ligament (ACL) injuries are a common and complex injury coupled with a lengthy rehabilitation. Goal setting is said to be an effective psychological tool within ACL rehabilitation due to its simplicity and is commonly used amongst sport and health professionals. To date, literature surrounding goal setting practices has only focused on qualified therapists. Purpose The central aim of this study was to explore UK student physiotherapists' perceptions towards goal setting practices u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Five studies examined the processes and practices of the goal setting conversation (Mullis & Hay, 2010; Pashley et al., 2010; Schoeb, 2009; Schoeb et al., 2014; Åsenlöf et al., 2005b). Three studies related to current training and physiotherapists' perceptions of their skills for goal setting (Alexanders, Chesterton, et al., 2021; Alexanders, Chesterton, et al., 2021; Keogh et al., 2018). Three studies attempted to match individually elicited goals to existing patient‐reported outcome measures (PROMs) (Blackburn & Kaplan, 2019; Soukup & Vøllestad, 2001; Stevens et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies examined the processes and practices of the goal setting conversation (Mullis & Hay, 2010; Pashley et al., 2010; Schoeb, 2009; Schoeb et al., 2014; Åsenlöf et al., 2005b). Three studies related to current training and physiotherapists' perceptions of their skills for goal setting (Alexanders, Chesterton, et al., 2021; Alexanders, Chesterton, et al., 2021; Keogh et al., 2018). Three studies attempted to match individually elicited goals to existing patient‐reported outcome measures (PROMs) (Blackburn & Kaplan, 2019; Soukup & Vøllestad, 2001; Stevens et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…1318 -GAYTON and MONGA Åsenlöf et al, 2004, 2005a, 2005b, 2009). Others referred to operant conditioning (Emilson et al, 2017;Linton et al, 1999;Ostelo et al, 2000;Pool et al, 2006), self-determination theory (Alexanders & Douglas, 2018;Gardner et al, 2018;Keogh et al, 2018) and goal setting theory (Alexanders, Chesterton, et al, 2021;Nicolson et al, 2018;Schoeb et al, 2014). Other…”
Section: Goal Setting Theoriesmentioning
confidence: 99%
See 2 more Smart Citations
“…From a curriculum perspective, undergraduate and postgraduate physiotherapy training is said to be inconsistent across the UK (Alexanders et al, 2020;Heaney et al, 2012). These inconsistencies are associated with insufficient content in certain areas, with limited psychological skill training being the main area of concern (Baddeley & Bithell, 1989;Holopainen et al, 2020).…”
mentioning
confidence: 99%